Y2O3:Eu and the Mössbauer isomer shift coefficient of Eu compounds from ab-initio simulations. (29th November 2021) - Davydov, Arkadiy; Sanna, Antonio; Concas, Giorgio
Abstract: We report on a full potential density functional theory characterization of Y2 O3 upon Eu doping on the two inequivalent crystallographic sites 24 d and 8 b . We analyze local structural relaxation, electronic properties and the relative stability of the two sites. The simulations are used to extract the contact charge density at the Eu nucleus. Then we construct the experimental isomer shift (IS) versus contact charge density calibration curve, by considering an ample set of Eu compounds: EuF3, EuO, EuF2, EuS, EuSe, EuTe, EuPd3 and the Eu metal. The, expected, linear dependence has a slope of α = 0.054 mm s −1 Å − 3, which corresponds to nuclear expansion parameter Δ R / R = 6.0 × 10 −5 . α allows to obtain an unbiased and accurate estimation of the IS for any Eu compound. We test this approach on two mixed-valence compounds Eu3 S4 and Eu2 SiN3, and use it to predict the Y2 O3 :Eu IS with the result +1.04 mm s −1 at the 24 d site and +1.00 mm s −1 at the 8 b site.